Case Report: Ophthalmologic Evaluation Over a Long Follow-Up Time in a Patient With Wolfram Syndrome Type 2: Slowly Progressive Optic Neuropathy as a Possible Clinical Finding - Di Iorio, Valentina; Mozzillo, Enza; Rosanio, Francesco Maria; Di Candia, Francesca; Genesio, Rita; Testa, Francesco; Iovino, Claudio; Franzese, Adriana; Simonelli, Francesca (Frontiers in Pediatrics, 2021)
Wolfram syndrome (WFS) is a rare autosomal recessive neurodegenerative disease whose diagnosis requires diabetes mellitus and OA. WFS includes a wide spectrum of other possible complications such as diabetes insipidus, sensorineural deafness, urinary tract problems, neurological and psychiatric disorders. Most WFS patients show type 1 syndrome (WFS1) caused by mutations in the WFS1 gene, encoding Wolframin protein, while few patients are affected by WFS type 2 (WFS2) due to a pathogenetic variants in the CISD2 gene encoding an endoplasmic reticulum intermembrane small protein. WFS2 is considered a phenotypic and genotypic variant of WFS, from which differs only for the increased risk of bleeding and presence of peptic ulcers. Optic atrophy and diabetes are considered cardinal features of WFS. We hereby report the ophthalmologic evaluation in a patient, previously described, with WFS2 after 8 years of follow-up. A 20-year-old white woman was referred to our retinal center for the first time in 2012 following a diagnosis of a novel intragenic exon 2 CISD2 homozygous deletion, for the suspicion of an associated bilateral optic atrophy. Fundus examination, spectral-domain optical coherence tomography, visual field, visual evoked potentials were performed and confirmed the presence of an optic neuropathy that remained stable over 8 years follow up. A slowly progressive optic neuropathy, rather than optic atrophy, can characterize patients with WFS2 and CISD2 intragenic deletion.